Greenspan's basic & clinical endocrinology - Gardner, David G.; Shoback, Dolores M. (New York : McGraw-Hill Education, 2018)
Greenspan's Basic & Clinical Endocrinology, Tenth Edition delivers a succinct, leading-edge overview of the underlying molecular biology of the endocrine system and the latest perspectives on the diagnosis and treatment of specific diseases and disorders. Featuring an enhanced design that includes hundreds of full-color illustrations and clinical photographs, Greenspan's is a true must-have during traditional or integrated courses in endocrinology, endocrinology rotation, or exam prep in internal medicine and endocrinology, as well as a reference for disease management. Greenspan's provides clinically relevant coverage of metabolic bone disease, pancreatic hormones and diabetes mellitus, obesity, and many other diseases and disorders. Supporting this important material is a handy appendix of normal hormone reference ranges across the lifespan -- Back cover.
Hormones and hormone action -- Endocrine autoimmunity -- Evidence-based endocrinology and clinical epidemiology -- Hypothalamus and pituitary gland -- The posterior pituitary (neurohypophysis) -- Growth -- The thyroid gland -- Metabolic gone disease -- Glucocorticoids and adrenal androgens -- Endocrine hypertension -- Adrenal medulla and paraganglia -- Testes -- Female reproductive endocrinology and infertility -- Disorders of sex development -- Puberty -- The endocrinology of pregnancy -- Pancreatic hormones and diabetes mellitus -- Hypoglycemic disorders -- Disorders of lipoprotein metabolism -- Obesity -- Humoral manifestations of malignancy -- Multiple endocrine neoplasia -- Transgender endocrinology -- Endocrine emergencies -- AIDSendocrinopathies -- Endocrine surgery -- Appendix : Normal hormone references ranges.
Includes bibliographical references and index.
Keywords: Endocrine Glands; Endocrine System Diseases; Hormones